Endocanabinóides modulam os efeitos inibitórios dos glicocorticóides sobre as respostas neuroendócrinas e comportamentais durante a lactação - Vilela, Fabiana Cardoso (2011)
It has been shown that glucocorticoids can modulate prolactin and oxytocin secretion, but the influence of glucocorticoids on the neuroendocrine and behavioral responses during lactation was not well known. Therefore, we evaluated the influence of dexamethasone (exogenous glucocorticoid) and hypothalamic-pituitary-adrenal axis activation by administration of LPS on the neuroendocrine and behavioral responses during lactation. In addition, we verified if the effects produced by glucocorticoids are mediated by endocannabinoids. For this purpose, we used a CB1 receptor antagonist (AM251) following the administration of dexamethasone. To confirm the possible involvement of the cannabinoid system on the neuroendocrine and behavioral responses during lactation, we used a CB1 receptor agonist (WIN 55,212-2). The dexamethasone treatment disrupted neuroendocrine and behavioral responses during lactation, because reduced oxytocin and prolactin, decreased maternal behavior as well as aggressive behavior, reduced litter weight gain, reverted the maternal anxiolysis and decreased the number of c-Fos positive neurons in the BST, MnPOv and MnPOd, and reduced the number of c-Fos/OT double labeled neurons in PVN and SON. The AM251 treatment reverted most of the effects produced by dexamethasone, suggesting the involvement of endocannabinoids in these effects. The changes in the endocrine and behavioral responses during lactation produced by administration of LPS are mediated by glucocorticoids, since metyrapone (glucocorticoids synthesis inhibitor) reverted some effects produced by LPS. The treatment with WIN 55,212-2 reduced the neuroendocrine and behavioral responses in lactating female rats, confirming our hypothesis that the effects of glucocorticoids are mediated by endocannabinoids. Taken together, our results suggest that dexamethasone treatment in lactating rats disrupts prolactin and oxytocin secretion, and this is followed by an attenuation of behavior responses and these effects are mediated by endocannabinoids.